Analysis of Agent Performance in Fostering Sharia Insurance Understanding of Prospective Customers of Pt.Prudential Life Assurance Binjai Branch - Ayu Lestari; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Sharia insurance is an effort to help or protect each other between fellow human beings. The funds contained in sharia insurance will be donated to sharia insurance participants when a risk or disaster befalls the customer. These funds are known as Tabarru funds, this will certainly minimize the risks that occur between sharia insurance customers. In an insurance company, both in terms of conventional and sharia insurance types, an agent is needed. The performance of an agent is certainly very influential on the progress or failure of an insurance company, as well as a liaison or mediator to prospective customers. whether or not when the prospect, as well as providing solutions to prospective customers when choosing a product suitable for him, is also a form of the agent's responsibility. The purpose of this study was to determine the performance of agents in developing understanding of sharia insurance against prospective customers of Pt.Prudential Life Assurance, Binjai Branch. This study used a qualitative method with data collection techniques using literature studies and interviews from several prospective customers.can help people understand the importance of insurance for the protection of themselves and their families, as well as customers free from the practice of usury..